Hormonal Profiles and Prevalence of Polycystic OvarySyndrome in Women with Acne - صالح حسن (Latakia University Journal -Medical Sciences Series, 2020)
One of the important etiologic factors in acne is an increase in sebaceous gland activity, which is androgen dependent. Acne is a common manifestation of hyperandrogenemia. Therefore, acne may not only cause cosmetic concern but may also be a sign of underlying disease. In females, the most common cause of hyperandrogenemia is polycystic ovary syndrome (PCOS). The purpose of this study was to determine the hormonal profiles of women with acne and the prevalence of PCOS in women attending the gynecological clinic referred from the dermatological clinic with acne problems. There were 51 women with acne; 20 regularly menstruating volunteers without acne served as a control group. Because of this high prevalence of PCOS in women with acne, all women presenting with acne should be asked about their menstrual pattern and examined for other signs of hyperandrogenemia. Hormonal profile determination as well as pelvic ultrasonography for ovarian visualization should be performed to confirm the diagnosis of PCOS in female acne patients who have menstrual disturbances.